Annotated Bibliography: Sexual Orientation and Gender Identity Issues in Educational Ministry - Severe, Michael K. (Christian education journal, 2021)
The following short annotated bibliography is a starting place for locating resources regarding sexual orientation and gender identity issues in educational ministry.